SUGGESTIONS ON THE APPLICATION OF CLUSTER TECHNOLOGIES AT THE MODERN STAGE OF DEVELOPMENT OF THE ECONOMY OF THE CITY OF MOSCOW - A. M. Kovalev; O. A. Afanasieva (Вестник университета)
The issues of creating and functioning cluster structures within the territory of the city of Moscow in various fields of activity and providing them with the appropriate infrastructure have been examined. The role of clusters in the field of strengthening cooperative ties in order to implement mutually beneficial business projects has been emphasized. Practical recommendations have been given, within the framework of the current regulatory and legal framework, on the creation of a rational system, that allows organizing selection into a cluster of business entities. Particular attention has been paid to microclusters, their types, roles and place in innovative processes; it has been proposed to use organizational, economic and administrative levers for their formation. The structure of the feasibility study (business plan) of the cluster project has been adduced. The necessity of developing the organizational and methodological base for the further implementation of cluster technologies has been noted.